DIFFERENCES IN DISPLAYING OF MOTOR ABILITY OF STRENGTH IN PRIMARY SCHOOL STUDENTS WHO ACTIVELY PLAY FOOTBALL AND THOSE WHO ARE NOT INVOLVED IN SPORTS ACTIVITIES - Jasmin Pandur; Almir Popo; Amar Tojaga (Sport Scientific And Practical Aspects, 2025)
Man consists of different abilities and traits. The degree of development and the level of achievement, as well as their mutual relationship, are different from person to person. Morphological characteristics are the characteristics responsible for the dynamics of growth and development, as well as for the characteristics of the body structure. Motor abilities are features that participate in solving motor tasks and that can be developed to a greater extent. We will find out the difference in these abilities between students active in football and physically inactive students through the results of this master's thesis. The goal of the research is to determine the differences between students who are actively engaged in football and those students who are not active in sports. The research was conducted on 52 subjects, students of an elementary school.